Effect of using bentonite during fermentation on protein stabilisation and sensory properties of white wine. (11th November 2013) - Lira, Eugenio; Salazar, Fernando N.; Rodríguez‐Bencomo, Juan J.; Vincenzi, Simone; Curioni, Andrea; López, Francisco
Summary The bentonite use to remove proteins from white wine is a widespread practice that prevents protein haze formation after bottling. However, an excess of bentonite can have negative effects on both the aromatic profile of young white wines and the quality of the foam of sparkling wines. Therefore, the optimisation of bentonite amount to be used and the moment of its application during winemaking to minimise wine quality losses are of great interest for winemakers. This paper analyses how applying an equal bentonite dose at different stages (must clarification; beginning, middle and end of fermentation) on two scales (industrial and pilot) affects the protein content and stability, physical–chemical characteristics, aromatic profile and foam quality of the obtained wines. No important differences in the oenological parameters were observed between industrial and pilot scales, whereas the scale of the experimental treatments affected protein stability, aroma composition and foam quality of the wines.